Implementation of a Mindfulness-Based Crisis Intervention for Frontline Healthcare Workers During the COVID-19 Outbreak in a Public General Hospital in Madrid, Spain - Rodriguez-Vega, Beatriz; Palao, Ángela; Muñoz-Sanjose, Ainoa; Torrijos, Marta; Aguirre, Pablo; Fernández, Arancha; Amador, Blanca; Rocamora, Cristina; Blanco, Laura; Marti-Esquitino, Jesús; Ortiz-Villalobos, Aránzazu; Alonso-Sañudo, Mónica; et al. (Frontiers in Psychiatry, 2020)
Introduction: The COVID-19 outbreak is having an impact on the well-being of healthcare workers. Mindfulness-based interventions have shown effectiveness in reducing stress and fostering resilience and recovery in healthcare workers. There are no studies examining the feasibility of brief mindfulness-based interventions during the COVID-19 outbreak. Materials and methods: This study is a quasiexperimental research with a post intervention assessment. We describe an on-site brief mindfulness intervention and evaluate its feasibility, safety and helpfulness. Results: 1,000 out of 7,000 (14%) healthcare workers from La Paz University Hospital in Madrid (Spain) participated in at least one session. 150 out of 1,000 (15%) participants filled out a self-report questionnaire evaluating the helpfulness of the intervention for on-site stress reduction. 92 subjects (61%) participated in more than one session. Most of the participants were women (80%) with a mean age of 38.6 years. Almost half of the sample were nurses (46%). Sessions were perceived as being helpful with a mean rating of 8.4 on a scale from 0 to 10. Only 3 people (2%) reported a minor adverse effect (increased anxiety or dizziness). Discussion: Our data supports the feasibility, safety and helpfulness of an on-site, brief mindfulness-based intervention designed to reduce stress for frontline health workers during a crisis. There is a need to continue testing this type of interventions, and to integrate emotion regulation strategies as an essential part of health workers’ general training.